Legitimacy and post-conflict state-building: the undervalued role of performance legitimacy. Issue 2 (4th March 2018) - Dagher, Ruby
Abstract: Legitimacy is essential to state-building after conflict. Yet, the prescribed path to gaining legitimacy is often a narrow one that borrows heavily from the experiences of Western states. Elections are prescribed as an essential first step on the logic that this means gaining process legitimacy can rebuild a social contract between citizens and the state, a social contract that is rooted in democratic norms and values. This article proposes an alternative path, one that emphasises the critical role of performance legitimacy and its non-exclusive nature. Performance legitimacy is granted when citizens perceive that some or all of their basic needs are being met. The article offers a new analytical framework for understanding a state's potential source of performance legitimacy, how non-state actors may vie with the state to seize this form of legitimacy, and what consequences this has for processes of state institution-building after conflict. In this respect, this article seeks to reorient theory and practice to a broader view of legitimacy and its critical role in post-conflict state-building.